Development of Audio-Assisted Picture Storybook Media Based On Character Education - Selirowangi, Nisaul Barokati; Mulyaningsih, Sefty Wahyu (STAI Miftahul Ula Nganjuk, 2025)
The purpose of this research is to develop character education-based audio-assisted picture storybook media for grade V elementary school students in order to instill positive character for the comfort and safety of students. The research method was carried out with the development model of Dick and Carey through ten stages of development in V Elementary School. Data collection techniques through observation and interviews, as well as distributing questionnaires to test the products produced. Data analysis was carried out qualitatively and quantitatively. Product validation is done through media experts and material experts. the validation results have an average value of 88% which is interpreted as very feasible. Based on the results of the validation, the researcher concluded that the character education-based audio-assisted picture storybook media is feasible as a medium in learning in character cultivation for fifth grade elementary school students.